Maximal oxygen uptake is associated with the snp 13470 G>C polymorphism of the mitochondrial NADH dehydrogenase subunit 5 gene (mtND5) in caucasians from Poland - Gronek, Piotr; Holdys, Joanna; Kryściak, Jakub; Stanisławski, Daniel (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Physical performance displays a great inter-individual variance in both general population and among well-trained athletes. Genetic factor has an important contribution in this variance. The aim of this study was to examine the association between maximal oxygen uptake and genetic variants of mitochondrial NADH dehydrogenase subunit 5 gene (mtND5) in Caucasians from Poland. Material and Methods. The studies were carried out in a group of 154 men and 85 women, professional athletes representing various sports and fitness levels and students of the University of Physical Education in Poznań. Physiological and molecular procedures were used, i.e. direct measurement of maximal oxygen uptake (VO2max) and SNP 13470 G>C polymorphism of the mitochondrial NADH dehydrogenase subunit 5 gene (mtND5) was determined by restriction fragments length polymorphism (PCR-RFLP). Results. We have found that maximal oxygen uptake is associated with BamHI+/+ homoplasmic variant of the mtND5 gene in Caucasians from Poland. We have also observed positive influence of BamHI+ allele on level of maximal oxygen uptake (VO2max)
Keywords: mtND5; athletic performance; endurance; genetic polymorphism; energy efficiency